Population Structure and Growth of the Threatened Pen Shell, Pinna rudis (Linnaeus, 1758) in a Western Mediterranean Marine Protected Area - NEBOT COLOMER, E.; VÁZQUEZ-LUIS, M.; GARCÍA-MARCH, J. R.; DEUDERO, S. (Mediterranean Marine Science, 2016)
Coastal ecosystems are being extensively degraded by human activities. Benthic, slow-growing and long-lived species are highly vulnerable to these impacts. Marine protected areas might avoid biodiversity losses through habitat protection. The pen shell Pinna rudis is a protected species, but scarce data are available on its ecology and biology. The present study is a comprehensive ecological study encompassing several unknown aspects of the growth and inner record in relation to habitat types, density and size distribution. A total of 418 strip transects were conducted by scuba diving in the Marine Protected Area of Cabrera National Park (39.14° N, 2.96° E), during the summers of 2011, 2012 and 2013. Sampling was conducted across different habitats and depths exploring 152,146.35 m2 in total. Densities varied spatially within the park (from 0 to 6.89 ind./100 m2) corresponding to a wide range of sizes and ages. Most pen shells were patchily distributed and mainly concentrated in caves. Two hotspots with high densities represent the highest densities ever recorded worldwide, showing a possible link to high larval accumulation and settlement. The population size structure showed a unimodal distribution with shell width ranging from 6.2 to 25.0 cm, with an average shell width of 16.0 ± 3.4 cm. The absolute growth was asymptotic, with a maximum age and length of 28-31 years and 45 cm, respectively. This study on the biology and ecology of a well-established population of Pinna rudis in the Western Mediterranean could set a baseline for the conservation of this species in other areas.